PENGARUH GAYA HIDUP, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK ORIFLAME - Fitriana; Yandri Sudodo; Lukmanul Hakim (Journal of Management and Business, 2019)
The research was attempted to analysis the influence of lifestyle, price and quality of the product on decision making upon the Oriflame cosmetics costumers in Sumbawa Region. The research involved primary and secondary data which quantitative method by using SPSS. The primary one was in the form of questionnaires which were given to Oriflame’s costumers in Sumbawa Region, while the secondary data were obtained from costumer data which have been collected by another party. by using purposive sampling, this research use 70 respondent. The result of the research showed that the variable of lifestyle has significant effect on purchase decision. The price variable has no significant effect on purchase decision, while variable quality of the product gave significant effect on costumers’ decision. Whereas, in simultaneously, the variable of lifestyle, the cost, and quality of the product have significant effect on costumers’ decision in purchasing the Oriflame Product in Sumbawa Region.